Pursuing Imperfection, Forgiveness, And Repentance In Popular Twenty-First Century Malay Television Fiction - Idrus, Mohd Muzhafar; Raihanah, MM; Hashim, RS (Ateneo De Manila Univ, 2024)
Indexed by SCOPUS/WOS